NILAI MORAL DALAM SERAT CARIYOSIPUN RARA KANDREMAN KASAMBETAN DONGENG TIGANG WARNI - Lestari, Suwasti Ratri Eni; Widyastuti, Sri Harti (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2024)
Serat Cariyosipun Rara Kandreman Kasambetan Dongeng Tigang Warni was written by Mas Nuswadiharja in 1874, printed in 1916 by Papyrus Batawi. Serat Cariyosipun Rara Kandreman Kasambetan Dongeng Tigang Warni tells about good and bad human traits. Which can be used as an example for the community in general. The purpose of this study is to describe the moral values in Serat Cariyosipun Rara Kandreman Kasambetan Dongeng Tigang Warni. This study uses qualitative descriptive research with philological studies. The object of this research is the moral values contained in the manuscript of Serat Cariyosipun Rara Kandreman Kasambetan Dongeng Tigang Warni by Mas Nuswadiharja. The data collection techniques used in this study are using library techniques and note-taking techniques. The handling of the Serat Rara Kandreman Kasambetan Dongeng Tigang Warni by transliterating from the Javanese script to the Latin script, then the content of the manuscript is analyzed so that the moral teachings contained in the manuscript can be understood. Based on the results of research and discussion on Serat Cariyosipun Rara Kandreman Kasambetan Dongeng Tigang Warni, the following conclusions can be drawn: (1) Moral values concerning human relationships with oneself, including: (a) self-control, (b) courage, (c) self-confidence, (d) acting carefully, (e) honesty, (f) leadership, (g) perseverance, (h) wisdom, and (i) hard work. (2) Moral values concerning human relationships with fellow human beings which include: (a) affection between fellow human beings, (b) caring for fellow human beings, (c) not liking to hold grudges, (d) maintaining good relations with others, (e) helping others, and (f) kinship and mutual cooperation. (3) Moral values concern the relationship between humans and the natural environment (utilizing nature as needed). (4) Moral values regarding man's relationship with God include: (a) belief in God, (b) man's closeness to God, (c) efforts to get closer to God, and (d) belief in destiny and death.Serat Cariyosipun Rara Kandreman Kasambetan Dongeng Tigang Warni ditulis oleh Mas Nuswadiharja pada tahun 1874, dicetak pada tahun 1916 oleh Papyrus Batawi. Serat Cariyosipun Rara Kandreman Kasambetan Dongeng Tigang Warni menceritakan tentang sifat-sifat manusia yang baik maupun buruk. Yang dapat dijadikan teladan bagi masyarakat secara umum. Tujuan penelitian ini adalah mendeskripsikan nilai-nilai moral dalam Serat Cariyosipun Rara Kandreman Kasambetan Dongeng Tigang Warni. Penelitian ini menggunakan penelitian deskriptif kualitataif dengan kajian filologi. Objek dari penelitian ini adalah nilai-nilai moral yang terkandung dalam naskah Serat Cariyosipun Rara Kandreman Kasambetan Dongeng Tigang Warni karya Mas Nuswadiharja. Pengumpulan data yang digunakan dalam penelitian ini adalah teknik pustaka dan teknik catat. Penanganan Serat Rara Kandreman Kasambetan Dongeng Tigang Warni dengan cara transliterasi dari aksara Jawa ke aksara Latin, kemudian analisis isi dilakukan untuk memahami ajaran moral yang tekandung dalam naskah. Berdasarkan hasil penelitian dan pembahasan terhadap Serat Cariyosipun Rara Kandreman Kasambetan Dongeng Tigang Warni dapat ditarik kesimpulan sebagai berikut: (1) nilai moral menyangkut hubungan manusia dengan diri sendiri, meliputi: (a) pengendalian diri, (b) pemberani, (c) percaya diri, (d) bertindak hati-hati, (e) kejujuran, (f) kepemimpinan, (g) ketekunan, (h) kebijaksanaan, serta (i) kerja keras. (2) Nilai moral menyangkut hubungan manusia dengan sesama manusia yang meliputi: (a) kasih sayang antarsesama manusia, (b) peduli dengan sesama manusia, (c) tidak suka menyimpan dendam, (d) menjaga hubungan baik dengan orang lain, (e) tolong menolong antarsesama, serta (f) kekeluargaan dan gotong royong. (3) Nilai moral menyangkut hubungan manusia dengan lingkungan alam (memanfaatkan alam sesuai kebutuhan). (4) Nilai moral menyangkut hubungan manusia dengan Tuhan meliputi: (a) percaya kepada Tuhan, (b) kedekatan manusia kepada Tuhan, (c) upaya mendekatkan diri kepada Tuhan, serta (d) percaya kepada takdir dan kematian.